Tabiat Manusia Dalam Al-Qur’an, Perumpamaan Lalat dan Tafsir Surah Al-Hajj ayat 73 Ṭanṭāwī Jauharī - Fitriani; Hasyim, Muh. Fathoni; Razi, Fahrur; Abdulfatah, Fikri (JOM, 2024)
This article examines the parable of the fly in the Qur'an, specifically in Surah Al-Hajj verse 73, and how this parable is used to describe human nature from the perspective of Ṭanṭāwī Jauharī in his tafsir, Tafsīr Al-Jawāhir fī Tafsīr Al-Qur'ān Al-Karīm. This research employs the library research method by collecting and analyzing various relevant literature sources, including books, journals, and other scholarly works. The analysis technique utilized is descriptive analysis, which involves the systematic collection, compilation, classification, analysis, and interpretation of data. The findings indicate that although flies are mentioned in a limited number of verses, this parable conveys profound wisdom about human nature. Analysis of Surah Al-Hajj verse 73 from Ṭanṭāwī Jauharī's perspective reveals that the fly in this parable reflects several human traits. First, it symbolizes human weakness in facing life's challenges, similar to the fly's lack of significant strength. Second, it illustrates man's dependence on Allah, akin to the fly's reliance on its environment for survival. Third, it highlights man's inability to create or alter anything without divine assistance, just as the fly cannot escape a simple trap. Ṭanṭāwī Jauharī's interpretation also underscores that the parable of the fly illustrates the insignificance of man in the face of Allah's greatness and the necessity for humans to recognize and accept their limitations. This article significantly contributes to understanding the relationship between parables in the Qur'an and human character, enriching the field of Qur'anic exegesis and Islamic ethical studies.